Opportunities and Challenges of Embedding AI in SINTA: A Systematic Literature Review - Surbakti, Feliks Prasepta Sejahtera (Metris: Jurnal Sains dan Teknologi, 2024)
The incorporation of Artificial Intelligence (AI) into Indonesia's Science and Technology Index (SINTA) offers both significant opportunities and challenges for advancing research management, evaluation, and development. This paper examines the advantages of embedding AI into SINTA, such as the ability to automate the identification of predatory journals, provide personalized research recommendations, and enhance the accuracy of institutional rankings. Furthermore, AI can help analyze citation trends, streamline the peer review process, and detect plagiarism or other forms of academic misconduct. However, this integration also brings several obstacles, including the need to ensure high-quality data, uphold transparency and fairness in AI-driven outcomes, protect data privacy, and address the substantial technological investments required. While AI holds the potential to greatly strengthen SINTA as a platform for overseeing and supporting research activities in Indonesia, overcoming these challenges is critical for its effective implementation. The study concludes that, with proper oversight and investment, integrating AI into SINTA could significantly boost the country's research ecosystem, fostering greater innovation and scientific productivity.